Emotions, future selves and the process of desistance - Hunter, Ben (The British journal of criminology, 2018)
Desistance research emphasizes that offenders identify a future self that aids desistance efforts. However, it is unclear how future selves operate when offending opportunities arise. To explore this, we employ qualitative accounts of instances when offenders and ex-offenders abstained from offending, and the emotions this evoked. Offending was avoided to preserve aspects of offenders’ lives or avoid negative consequences but, for some, avoiding offending brought frustration. Finally, those who had made the most progress towards desistance were less likely to identify opportunities for offending. These findings suggest future selves inform the desistance process, highlighting particular ways to be. However, time is needed to build up valued aspects of the life that may be feared lost if engaging in crime. Before the benefits of abstaining are recognized, there may be a tension between the future and current self.